Physical Asset Management - Hastings, Nicholas A.J. (Springer, 2015)
Physical asset management is the management of fixed assets such as machinery, vehicles, equipment, plant, buildings, and infrastructure. This book presents a systematic approach to the management of these assets from concept to disposal. It makes particular reference to the ISO 55000 series of asset management standards. It is designed to be suitable as: • A textbook for a course in asset management to senior undergraduate or graduate students in asset management, engineering management, public works engineering, systems engineering, industrial engineering, maintenance engineering or operations management. • A reference point for engineers and managers working in the asset management field. • An introduction to ISO55000 and a reference point for the techniques required to implement this standard. The book introduces the general principles of physical asset management, covering all stages of the asset life cycle. This starts with initial business appraisal and proceeds through identification of fixed asset needs, capability gap analysis, financial evaluation, logistic support analysis, life cycle costing, management of in-service assets, maintenance strategy, outsourcing, budgeting, cost-benefit analysis, disposal, and renewal. Industries to which this is applicable include: manufacturing; distribution; mining; electricity generation and supply; oil and gas; water; roads; railways; aviation; shipping; hospitals; retail centers; defense material; recreation and sporting facilities and local government. The chapters in this book are designed to introduce material in a logical sequence. As a whole year educational program it is suggested that Chaps. 1–16 provide material for the first semester and Chaps. 17–29 provide material for the second semester.
With an Introduction to ISO55000